Virtual Imaging System - Wang, Lulu (Auckland University of Technology, 2009)
The main purpose of this research project was to implement a combination of computer graphics and processing to generate displays that will aid in the visualization of the colour rendering properties of a range of light sources, including the new generation of high-output LEDs (light emitting diodes) that are becoming widely adopted in general lighting service. The CIE (International Commission on Illumination) has developed a colour appearance model CIECAM02 for use in colour imaging and colour management, and this model is utilized in this work. This thesis describes the design and construction of a computer-based model that can be used as a research tool for the simulation and demonstration of the colour rendering properties of various artificial light sources. It is a comprehensive study of the colour models and measurement procedures currently in use in the lighting industry, as recommended by the CIE. This research project focused on the display of a set of surface colour patches as if they were illuminated by a specific light source, and the simultaneous display of two such sets to demonstrate the surface colour differences arising from the use of the two different light sources. A VIS (virtual imaging system) has been developed to display the colour properties of a series of test colour samples under different light sources. This thesis describes the computer models developed for the representation and display of surface colours in general, and colour rendering in particular. The designed system computes and displays the colour of each sample from a knowledge of the light-source spectrum and the spectral reflectance of each surface. It can simultaneously display the colours resulting from illumination by two different sources. In addition, the system computes the colour appearance differences for two sets of colours using the CIECAM02 colour appearance model. Subjective and objective tests were taken to validate the computed results. The VIS has been designed and implemented. It also has been tested by 21 observers and we believe that it will be a powerful research tool for the lighting industry, especially in relation to colour rendering.
Keywords: LED; Computer modelling; Artificial lighting; Colour rendering